Analisis Rasio Keuangan pada Kinerja Keuangan Perusahaan Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2019-2023 - Vika Kurnia Guntari; Meilani Purwanti (Economic Reviews Journal, 2024)
This research aims to analyze the financial ratios that affect the company’s financial performance. The research method used is quantitative descriptive. The population in this study is all manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. Furthermore, listed companies continuously publish their reports in succession, have complete data regarding financial reports, preferred, dividends, and number of outstanding shares, as well as positive company financial ratios in the 2019-2023 period as samples in this research. The number of samples is 17 companies, so the total observations during the 2019-2023 period are 85. Based on the research results, it shows that liquidity ratios, solvency ratios, activity ratios, market valuation ratios have a significant influence on the company’s financial performance. This identifies that companies that can manage these four financial ratios well tend to have better financial performance.